2017
DOI: 10.1097/01.nep.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Student Perceptions of Structural Empowerment

Abstract: To meet role expectations for nurses, nurses must feel empowered. Faculty contributions to the learning environment for nursing students are critical. A descriptive analysis of student perceptions of empowerment within the learning environment was conducted using a form of Kanter’s Conditions of Work Effectiveness Questionnaire; 203 participants from schools in 17 different states completed surveys. Subjects demonstrated moderate degrees of structural empowerment in their learning environment. This positive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In a study conducted in the United States, student nurses were found to have a moderate degree of empowerment (Ward, 2017). Starting to teach them young about empowerment will improve their empowerment levels as they grow older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the United States, student nurses were found to have a moderate degree of empowerment (Ward, 2017). Starting to teach them young about empowerment will improve their empowerment levels as they grow older.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the United States, student nurses were found to have a moderate degree of empowerment (Ward, 2017).…”
Section: Relationships Of Demographics Qualities and Performances Of Empowered Nursesmentioning
confidence: 99%
“…The CWEQ II was developed by Laschinger, Finegan, Shamian, & Wilk 17 and has been widely used to examine the correlation between the nurses' reported level of SE and other nursing practice parameters. 15 , 18 , 19 The tool consisted of 19 semantic scale items and examines the nurses' perceived level of SE in four subscales (domains), which collectively underpin the level of empowerment according to kanter's theory of SE. 17 These domains are opportunity, information, support, and resources.…”
Section: Methodsmentioning
confidence: 99%
“…GNSs' assessments were the highest in the category of Expertise (VAS 68.7-72.2; mean 70.6, SD 15.1) and the lowest in the category of Sociability (VAS 46.2-62.7; mean 55.7, SD 21.6) (Table 1). 3 Finland p < 0.0001, 4 Spain p < 0.01, 5 Italy p < 0.01, 6 Slovakia p < 0.01, 7 Portugal p < 0.01, 8 Finland p < 0.01, and 9 Italy p < 0.05.…”
Section: Level Of Empowermentmentioning
confidence: 95%
“…New nurses with a high competence are needed to respond to these challenges [1,6]. To be able to meet the role expectations of a registered nurse, nursing students must feel empowered already at graduation, in the very beginning phase of their nursing career [7]. However, there are only a few studies focusing on nursing students' empowerment [8].…”
Section: Introductionmentioning
confidence: 99%